MHC-mismatched Allotransplantation of Induced Pluripotent Stem Cell-derived Cardiomyocyte Sheets to Improve Cardiac Function in a Primate Ischemic Cardiomyopathy Model. Issue 8 (August 2019) - Kashiyama, Noriyuki; Miyagawa, Shigeru; Fukushima, Satsuki; Kawamura, Takuji; Kawamura, Ai; Yoshida, Shohei; Eiraku, Seiko; Harada, Akima; Matsunaga, Keiko; Watabe, Tadashi; Toda, Koichi; Hatazawa, Jun; et al.
Abstract : Background: Although allogeneic-induced pluripotent stem cell (iPSC)-derived cardiomyocytes (CMs) exhibit potential in cardiomyogenesis for heart failure, whether major histocompatibility complex (MHC)-matched allogenic iPSC implantation (MMAI) minimizes immune rejection for cell survival or functional recovery remains unknown. We herein explored whether MMAI with an iPSC-CM sheet is stable for a longer period and therapeutically more effective than MHC-mismatched AI in a primate ischemic cardiomyopathy model. Methods: Green fluorescent protein-transfected iPSC-CM sheets, derived from cynomolgus macaques with homozygous MHC haplotypes ''HT1, '' were transplanted on the left ventricle, generated by ligating the left anterior descending artery for 2 weeks in an ischemic model with or without heterozygous HT1 as MMAI and MHC-mismatched AI. Sham models were made by opening the chest at 14 days after left anterior descending ligation without any treatment. Results: Stereomicroscopy revealed that at 4 months after transplantation, green fluorescent protein intensity was higher in the MMAI group than in the MHC-mismatched AI group and the sham group. Immunohistochemistry staining revealed that host immune reaction with CD3-positive cells was stronger in MHC-mismatched AI than in MMAI at 3 months. Cardiac function improved both in MMAI and MHC-mismatched AI at 1 month after transplantation and was preserved until 6 months, whereas in the sham group, functional deterioration progressed over time. Conclusions: Although MHC-homo-iPSCs are preferred to avoid immune rejection, MHC-mismatched iPSC-CMs can also induce comparable cardiac functional recovery at late follow-up, suggesting that MHC-mismatched iPSC-based cardiac regenerative therapy with immunosuppressants is a feasible option for treating heart failure in clinical settings. Abstract : Supplemental Digital Content is available in the text.